2015
DOI: 10.1073/pnas.1421997112
|View full text |Cite
|
Sign up to set email alerts
|

Robust network oscillations during mammalian respiratory rhythm generation driven by synaptic dynamics

Abstract: How might synaptic dynamics generate synchronous oscillations in neuronal networks? We address this question in the preBötzinger complex (preBötC), a brainstem neural network that paces robust, yet labile, inspiration in mammals. The preBötC is composed of a few hundred neurons that alternate bursting activity with silent periods, but the mechanism underlying this vital rhythm remains elusive. Using a computational approach to model a randomly connected neuronal network that relies on short-term synaptic facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 55 publications
4
54
1
Order By: Relevance
“…Finally, to conceptualize how these features lead to the emergence of synchronous bursting initiated by spontaneous action potential firing we have built upon the results of Guerrier et al (42) to describe our excitatory network with a model based on random, sparse synaptic connections equipped with short-time synaptic plasticity (STSP), three synaptic vesicle pools, and a mechanism linking vesicle maintenance and recovery rates to energetic substrate availability. In our implementation of this computational model we explored the possibility of simplifying STSP dynamics further and found that the assumption of just a single vesicle pool ( Fig.…”
Section: Glucose Depletion Reduces Synchronous Burst Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, to conceptualize how these features lead to the emergence of synchronous bursting initiated by spontaneous action potential firing we have built upon the results of Guerrier et al (42) to describe our excitatory network with a model based on random, sparse synaptic connections equipped with short-time synaptic plasticity (STSP), three synaptic vesicle pools, and a mechanism linking vesicle maintenance and recovery rates to energetic substrate availability. In our implementation of this computational model we explored the possibility of simplifying STSP dynamics further and found that the assumption of just a single vesicle pool ( Fig.…”
Section: Glucose Depletion Reduces Synchronous Burst Ratementioning
confidence: 99%
“…We simulated a modified version of the excitatory neural network model described by Guerrier et al (42) consisting of 20x20 (400) connected neurons organized on a square lattice.…”
Section: Computational Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no clear mechanism for burst termination, and therefore rhythmicity, was found. Recent computational work suggests that rhythm generation can be driven by mixed short-term synaptic dynamics of excitatory connections [58]**. In the model, the initiation of inspiratory bursts depends on synaptic facilitation, whereas early-stage depression terminates the bursts and late-stage depression produces the refractoriness of the neurons between bursts.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms commonly found in rhythm generating networks include reciprocal inhibition [26 • ,27,28], rhythmic pacemaker properties [11 • ,2933] and recurrent excitatory network mechanisms [10,34 • ,35,36 • ]. However, their roles within a given network vary and are often different than originally hypothesized.…”
Section: Introductionmentioning
confidence: 99%